Analisis Pertumbuhan Ekonomi Provinsi Jawa Barat Periode Tahun 2010-2020 - Hamzah, Risna Amalia (Jurusan Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Siliwangi, 2021)
This study aims to analyze and determine the effect of inflation, interest rates, unemployment on economic growth in West Java Province. The data used is secondary time series data for the period 2010 â€“ 2020. The data is sourced from the Central Statistics Agency of West Java Province and Bank Indonesia. Data analysis was carried out using a quantitative approach with multiple linear regression model equations. The results of the study show that simultaneously (F test) inflation, interest rates and unemployment have a significant effect on economic growth in West Java Province. Partially (t test) inflation has a positive and insignificant effect on the economic growth of West Java province. The interest rate variable has a positive and significant effect on economic growth in the province of West Java. The unemployment variable has a negative and significant effect on the economic growth of the province of West Java.Â Penelitian ini bertujuan untuk menganalisis dan mengetahui pengaruh inflasi, suku bunga, pengangguran terhadap pertumbuhan ekonomi Provinsi Jawa Barat. Data yang digunakan adalah data sekunder time series selama periode tahun 2010â€“2020. Data bersumber dari Badan Pusat Statistik Provinsi Jawa Barat dan Bank Indonesia. Analisis data dilakukan dengan pendekatan kuantitatif dengan persamaan model regresi linier berganda. Hasil penelitian menunjukkan bahwa secara simultan (uji F) inflasi, suku bunga dan pengangguran berpengaruh signifikan terhadap pertumbuhan ekonomi Provinsi Jawa Barat. Secara parsial (uji t) inflasi memiliki pengaruh positif dan tidak signifikan terhadap pertumbuhan ekonomi Provinsi Jawa Barat. Variabel suku bunga berpengaruh positif dan signifikan terhadap pertumbuhan ekonomi Provinsi Jawa Barat. Variabel pengangguran berpengaruh negatif dan signifikan terhadap pertumbuhan ekonomi Provinsi Jawa Barat.